Nilai-Nilai Keislaman Dalam Novel Harry Potter and The Deathly Hallows (Analisis Semiotik) (Thaqafiyyat : Jurnal Bahasa, Peradaban dan Informasi Islam, 2016)
An author of a literary work tends to bring the moral values based on his/her religious background. A literary work, however, can be analyzed using different religious perspective. This research aims to reveal the values in Harry Potter and the Deathly Hallows novel through the Islamic perspective. Moreover, the values found in the novel are then interconnected to several issues of Muslims in Indonesia as one of the countries which translate the novel. This research applies the Semiotic theory by adopting ‘Peircean Sign’. The Islamic approach in this research applies Arifin’s view about dimension of Islamic values. This research results that there are several Islamic values in Harry Potter and the Deathly Hallows novel which are divided into three dimensions of life: (1) the dimension which contains the values in gaining life prosperity in the world; (2) the dimension which contains the values to motivate human in gaining happiness in the hereafter; and (3) the dimension which contains the values to compile both the world life and the hereafter importance. Furthermore, from the Islamic values, some of them have relevance with several issues of Muslim in Indonesia. According to the analysis, the writer concludes that Islamic values – as part of general values – can exist in every literary work. Besides that, Jews, Christian, and Islam claim that religious values in Harry Potter and the Deathly Hallows novel are in accordance with each religion. It shows that in fact, there is a relation among the three religions.